Addressing the security-development nexus in post-conflict situations. The role of construction in rebuilding strife-torn countries (2012)
The scholarly debate on the motives of civil conflict has been driven by explanations based on greed and grievance. Empirically, it has been demonstrated that greed explains the onset of conflict.Therefore, in order to prevent the renewal of civil war, the opportunity cost of the rebels going back to conflict must be raised in post-conflict situations. The central argument of this paper is to address this issue by promoting the construction sector as a tool to create development and achieve security.